Water scarcity and solar desalination systems in the eastern mediterranean region: A case of northern cyprus - Agboola, Philips Olaleye; Egelio?lu, Fuat (My University, 2011)
The constant decline of renewable water in the Middle East and North Africa (MENA) and the Mediterranean regions qualify these two regions the most water scarce in the world. Water scarcity can be defined as a situation where there is not enough water to meet all local demand. These demands may include water needed for ecosystems, agricultural and domestic use. Water is definitely physically scarce in the MENA and the Mediterranean regions with less than 1000 m3/capita/year and the scarcity is related to domestic water, fresh water for drinking and water for food production. Water scarcity in these regions is a function of both water supply and water demand as both applies in most of the countries. Using the Falkenmark indicator the Mediterranean regions will see increased deterioration in the availability of renewable water and more people will suffer the effects of water shortage. The area will face major constraints in meeting water requirements for agriculture in the coming decades. The severe impacts of the non-availability of renewable water in these regions are cushioned by the development of desalination technology that is at an advanced stage in most of the countries in the region. Water desalination technology provides unlimited and constant supply of high quality water, and reduces the pressure on freshwater ecosystems and groundwater resources. Selection of the appropriate desalination technology, use of renewable energy and a proper method of dealing with high salinity wastewater discharge are very important measures necessary to mitigate the negative impacts of desalination activity, reduce desalination costs and make desalination sustainable and reliable. This work reviews the nature of water scarcity in the Eastern Mediterranean region and advances in solar desalination using the Northern part of Cyprus as a case study. Copyright © 2011 by ASME.
ASME 2011 5th International Conference on Energy Sustainability, ES 2011 --
Keywords: Desalination technologies; Eastern Mediterranean; Freshwater ecosystem; High salinity wastewaters; Mediterranean region; Middle East and North Africa; Solar desalination systems; Use of renewable energies; Agriculture; Climate change; Desalination; Ecosystems; Groundwater; Sustainable development; Water filtration; Water supply; Potable water